2005
DOI: 10.1016/j.eururo.2005.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The 5α-Reductase Type II A49T and V89L High-Activity Allelic Variants are More Common in Men with Prostate Cancer Compared with the General Population

Abstract: ObjectivesTo compare men with prostate disease with those from the general population regarding polymorphisms in the androgen receptor gene and in the 5α-reductase II (SRD5A2) gene. Materials and MethodsThe SRD5A2 polymorphisms A49T, V89L and R227Q, the androgen receptor CAG and GGN repeats and sex hormone status was investigated in men with prostate cancer (CaP) (n=89), benign prostate hyperplasia (n=45) and healthy military conscripts (n=223). ResultsThe SRD5A2 high-activity allele variants A49T AT and V89L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…[27][28][29][30] In our study, we confirm a lack of association between V89L and risk of prostate cancer. The metaanalysis could not exclude the possibility of an association between the A49T polymorphism and risk of prostate cancer, as confirmed in our study.…”
Section: Discussionsupporting
confidence: 74%
“…[27][28][29][30] In our study, we confirm a lack of association between V89L and risk of prostate cancer. The metaanalysis could not exclude the possibility of an association between the A49T polymorphism and risk of prostate cancer, as confirmed in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Controversies remain regarding the association of this polymorphism with the risk of prostate cancer. Studies have reported a decreased risk of prostate cancer associated with the LL genotype (26,27), an increased risk with the LL genotype (28,29) or no association with risk and this genotype (17,30).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity of SRD5A is highly modulated by single-nucleotide polymorphisms (SNPs) located in these genes (Giwercman et al 2005;Cussenot et al 2007). These genetic variations in key genes belonging to the androgen pathway seem to be important for the prostate response to androgens (Lindstrom et al 2006).…”
Section: Introductionmentioning
confidence: 99%